Synthesis of MCM-41 Silica Mesoporous Modified with Zn Metal - Samriani Samriani; Muhammad Zakir; Paulina Taba; Nursiah La Nafie; Iin Indriani (Jurnal Kimia Sains dan Aplikasi, 2022)
MCM-41 and Zn-MCM-41 were successfully synthesized using hydrothermal and impregnation methods. The synthesized silica mesoporous was confirmed by characterizing the material using XRD, SEM-EDS, and BET-BJH analyses. XRD results showed three main peaks at angles of 2θ = 2.40° (100), 3.87° (200), and 4.49° (210), which are characteristics of mesoporous materials with hexagonal structures. SEM analysis showed that the surface morphology of Zn-modified MCM-41 formed aggregates of smaller particles. The EDS results showed that the amount of Zn in MCM-41 was 1.25%. Modification with Zn metal also affected the surface area and porosity of MCM-41, where the surface area, pore volume, and pore diameter decreased. Based on the adsorption-desorption analysis of N2 gas, both materials exhibit a type IV isotherm typical for mesoporous materials with an H1 hysteresis loop.